Association of bilateral salpingo-oophorectomy with all cause and cause specific mortality: population based cohort study. (8th December 2021) - Cusimano, Maria C; Chiu, Maria; Ferguson, Sarah E; Moineddin, Rahim; Aktar, Suriya; Liu, Ning; Baxter, Nancy N
Abstract: Objectives: To determine if bilateral salpingo-oophorectomy, compared with ovarian conservation, is associated with all cause or cause specific death in women undergoing hysterectomy for non-malignant disease, and to determine how this association varies with age at surgery. Design: Population based cohort study. Setting: Ontario, Canada from 1 January 1996 to 31 December 2015, and follow-up to 31 December 2017. Participants: 200 549 women (aged 30-70 years) undergoing non-malignant hysterectomy, stratified into premenopausal (<45 years), menopausal transition (45-49 years), early menopausal (50-54 years), and late menopausal (≥55 years) groups according to age at surgery; median follow-up was 12 years (interquartile range 7-17). Exposures: Bilateral salpingo-oophorectomy versus ovarian conservation. Main outcomes measures: The primary outcome was all cause death. Secondary outcomes were non-cancer and cancer death. Within each age group, overlap propensity score weighted survival models were used to examine the association between bilateral salpingo-oophorectomy and mortality outcomes, while adjusting for demographic characteristics, gynaecological conditions, and comorbidities. To account for comparisons in four age groups, P<0.0125 was considered statistically significant. Results: Bilateral salpingo-oophorectomy was performed in 19%, 41%, 69%, and 81% of women aged <45, 45-49, 50-54, and ≥55 years, respectively. The procedure was associated with increased rates of all cause death in women aged <45 years (hazard ratio 1.31, 95% confidence interval 1.18 to 1.45, P<0.001; number needed to harm 71 at 20 years) and 45-49 years (1.16, 1.04 to 1.30, P=0.007; 152 at 20 years), but not in women aged 50-54 years (0.83, 0.72 to 0.97, P=0.018) or ≥55 years (0.92, 0.82 to 1.03, P=0.16). Findings in women aged <50 years were driven largely by increased non-cancer death. In secondary analyses identifying a possible change in the association between bilateral salpingo-oophorectomy and all cause death with advancing age at surgery, the hazard ratio gradually decreased during the menopausal transition and remained around 1 at all ages thereafter. Conclusion: In this observational study, bilateral salpingo-oophorectomy at non-malignant hysterectomy appeared to be associated with increased all cause mortality in women aged <50 years, but not in those aged ≥50 years. While caution is warranted when considering bilateral salpingo-oophorectomy in premenopausal women without indication, this strategy for ovarian cancer risk reduction does not appear to be detrimental to survival in postmenopausal women.